Fabrication and Degradation of Electrospun Scaffolds from L-Tyrosine-Based Polyurethane Blends for Tissue Engineering Applications. (19th February 2012) - Spagnuolo, Michael; Liu, Lingyun
Abstract : It is important to control the degradation rate of a tissue-engineered scaffold so that the scaffold will degrade in an appropriate matching rate as the tissue cells grow in. A set of potential tissue engineering scaffolds with controllable rates of degradation were fabricated from blends of two biocompatible, biodegradable L-tyrosine-based polyurethanes (PEG1000 -HDI-DTH and PCL1250 -HDI-DTH) using the electrospinning process. The scaffolds were characterized by mat morphology, fiber diameter, diameter distribution, pore size, and hydrolytic degradation behavior. The majority of the scaffolds, despite having radically different chemical compositions, possessed no statistical difference with pore sizes and fiber diameters. The degradation pattern observed indicated that scaffolds consisting of a greater mass percentage of PEG1000 -HDI-DTH decayed to a greater extent than those containing higher concentrations of PCL1250 -HDI-DTH. The degradation rates of the electrospun scaffolds were much higher than those of the thin cast films with same compositions. These patterns were consistent through all blends. The work demonstrates one practical method of controlling the degradation of biopolymer scaffolds without significantly affecting an intended morphology.